Issues in media : selections from CQ Researcher. - CQ Press (Sage, 2019)
Overview: For current coverage of controversial and important issues centering on media, look to the balanced reporting, completer overviews and engaging writing that CQ Researcher has consistently provided for more than eighty years. This brief reader allows students to see the links among media, culture, business and politics. Each article gives substantial background as well as current analysis of the issue, in addition to the following special features: a pro/con box that examines two competing sides of a single question; a detailed chronology; an annotated bibliography and Web resources; photos, charts, graphs and maps